Efficacy of free and encapsulated natural antioxidants in oxidative stability of edible oil: Special emphasis on nanoemulsion-based encapsulation. (September 2019) - Sharma, Simran; Cheng, Sit-Foon; Bhattacharya, Bhaswati; Chakkaravarthi, S.
Abstract: Background: Degradation of edible oil by oxidation during the processing, storage, and heating has long been recognized as a major concern in the edible oil industry. The edible oil degradation leads to undesirable taste, odor, nutrient loss, and production of toxic compounds. The synthetic antioxidants are mostly used by the edible oil industry for preventing oxidation of the edible oil, due to its low cost and high antioxidant activity. However, synthetic antioxidants have detrimental health effects. Hence, the natural antioxidants are considered as the safer alternative to synthetic antioxidants. But, the low stability and loss of antioxidativity during heat processing limit the application of natural antioxidant in edible oil. Scope and approach: This review presents a brief overview of the effect of directly added free natural antioxidant and encapsulated natural antioxidant on oxidative stability of the edible oil, and different types of encapsulation methods for maintaining stability and antioxidativity of natural antioxidants in edible oil. A special focus has been attributed to nanoemulsion as it is being explored to encapsulate natural antioxidant. Key findinags and conclusions: The nanoemulsion-based encapsulation of natural antioxidant is an efficient method for increasing the antioxidativity, dispersibility, stability, and solubility of the natural antioxidants. The encapsulated natural antioxidant improves the oxidative stability of the edible oil, due to their controlled release and protected antioxidativity in the edible oil. In comparison to other encapsulation methods, the nanoemulsion technique is more promising as it provides nontoxic, tunable rheology and high physically stable emulsion. Highlights: Natural antioxidants are safe alternative to synthetic antioxidants in edible oil. Directly added natural antioxidant loses its antioxidativity during heating in oil. Encapsulation enhances stability and antioxidativity of natural antioxidant in oil. Methods of encapsulation of natural antioxidant have been reviewed. Role of nanoemulsion in preventing oxidation of oil have been spotlighted.